Treatment Outcomes and Dose Rate Effects Following Gamma Knife Stereotactic Radiosurgery for Vestibular Schwannomas. Issue 6 (4th July 2019) - Smith, Deborah Ruth; Saadatmand, Heva Jasmine; Wu, Cheng-Chia; Black, Paul J; Wuu, Yen-Ruh; Lesser, Jeraldine; Horan, Maryellen; Isaacson, Steven R; Wang, Tony J C; Sisti, Michael B
Abstract: BACKGROUND: Gamma Knife radiosurgery (GKRS; Elekta AB) remains a well-established treatment modality for vestibular schwannomas. Despite highly effective tumor control, further research is needed toward optimizing long-term functional outcomes. Whereas dose-rate effects may impact post-treatment toxicities given tissue dose-response relationships, potential effects remain largely unexplored. OBJECTIVE: To evaluate treatment outcomes and potential dose-rate effects following definitive GKRS for vestibular schwannomas. METHODS: We retrospectively reviewed 419 patients treated at our institution between 1998 and 2015, characterizing baseline demographics, pretreatment symptoms, and GKRS parameters. The cohort was divided into 2 dose-rate groups based on the median value (2.675 Gy/min). Outcomes included clinical tumor control, radiographic progression-free survival, serviceable hearing preservation, hearing loss, and facial nerve dysfunction (FND). Prognostic factors were assessed using Cox regression. RESULTS: The study cohort included 227 patients with available follow-up. Following GKRS 2-yr and 4-yr clinical tumor control rates were 98% (95% CI: 95.6%-100%) and 96% (95% CI: 91.4%-99.6%), respectively. Among 177 patients with available radiographic follow-up, 2-yr and 4-yr radiographic progression-free survival rates were 97% (95% CI: 94.0%-100.0%) and 88% (95% CI: 81.2%-95.0%). The serviceable hearing preservation rate was 72.2% among patients with baseline Gardner-Robertson class I/II hearing and post-treatment audiological evaluations. Most patients experienced effective relief from prior headaches (94.7%), tinnitus (83.7%), balance issues (62.7%), FND (90.0%), and trigeminal nerve dysfunction (79.2%), but not hearing loss (1.0%). Whereas GKRS provided effective tumor control independently of dose rate, GKRS patients exposed to lower dose rates experienced significantly better freedom from post-treatment hearing loss and FND ( P = .044). CONCLUSION: Whereas GKRS provides excellent tumor control and effective symptomatic relief for vestibular schwannomas, dose-rate effects may impact post-treatment functional outcomes. Further research remains warranted.